2022
DOI: 10.1128/msystems.01516-21
|View full text |Cite
|
Sign up to set email alerts
|

Endosymbionts Reduce Microbiome Diversity and Modify Host Metabolism and Fecundity in the Planthopper Sogatella furcifera

Abstract: Endosymbionts can profoundly affect the nutrition, immunity, development, and reproduction of insect hosts, but the effects of multiple endosymbiont infections on microbiota and the interaction of these effects with insect host fitness are not well known. By establishing S. furcifera lines with different endosymbiont infection status, we found that Cardinium and the combined Cardinium + Wolbachia infections differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 73 publications
(97 reference statements)
2
14
0
Order By: Relevance
“…A number of studies also have revealed the role of bacterial microorganisms in host development through participating in host metabolism or providing metabolites to the host 56,57 . For example, the bacterial microbiota can provide amino acids and B vitamins to the host 58–60 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies also have revealed the role of bacterial microorganisms in host development through participating in host metabolism or providing metabolites to the host 56,57 . For example, the bacterial microbiota can provide amino acids and B vitamins to the host 58–60 .…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies also have revealed the role of bacterial microorganisms in host development through participating in host metabolism or providing metabolites to the host. 56,57 For example, the bacterial microbiota can provide amino acids and B vitamins to the host. [58][59][60] Bacterial loads in the ovaries increased after tetracycline treatment, possibly providing the host with higher levels of bacterial metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not clear which pathways (tolerance, resistance) are involved in the double-infested host. In another study, the manipulative experiments established double-infected S. furcifera [23]; the study con rmed the effect of symbionts on metabolites (e.g. arginine biosynthesis and nicotinamide metabolism).…”
Section: Introductionmentioning
confidence: 90%
“…The relative copy number of the P450 gene was determined according to a method by Li et al 29 First, the DNA of 10 unmated female adults on the 1 d after emergence was extracted according to the CTAB method. 29 After the concentration and quality of the extracted DNA were determined, the relative copy numbers of CYP6FJ3 and CYP6CS3 were measured by qRT−PCR with the NovoStart SYBR qPCR SuperMix Plus kit in a 20 μL total reaction volume containing 200 ng of DNA, 10 μL of reaction buffer, and 1 μL each of 10 μM forward and reverse primer (CYP6FJ3CF: GTGTTCTCCAAA-AATGGCCGA; CYP6FJ3CR: CCGGATCGTTTTCTTTGAGCA. CYP6CS3CF: GTTCACTCCCAAAGAGACGGA; CYP6CS3CR: GGCGCCTTTGTCGATTGTATC) following the manufacturer's instructions with 3 biological and technical replicates per treatment.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%